Pengaruh Kompetensi dan Motivasi terhadap Kinerja Pegawai Personil Biro Rena Polda Kepulauan Bangka Belitung - Iwan Hermawan (MAMEN: Jurnal Manajemen, 2025)
The Indonesian National Police is a state instrument that plays a role in maintaining public security and order, as well as providing protection which is expected to provide good performance in the community. The purpose of this study was to determine the effect of competence and motivation on the performance of employees of the Bangka Belitung Islands Police Rena Bureau both partially. This type of research is quantitative research. Hypothesis testing is done with multiple regression tests. The sampling technique used is total sampling. The sample of this study were all personnel employees of the Rena Bureau of the Bangka Belitung Islands Police totaling 49 people. The research model is hypothesis testing, which tests the theoretical truth built by researchers. The research model is hypothesis testing, which tests the theoretical truths built by researchers. The data used are cross-sectional (observational research type) collected from research respondents, namely employees of the Bangka Belitung Islands Police Rena Bureau. Data processing uses SPSS software version 24. Data analysis techniques use classical assumption tests, multiple linear regression analysis, hypothesis testing and coefficient of determination testing. The results showed that partially competence and motivation affect the performance of employees of the Bangka Belitung Islands Police Rena Bureau.